Microbe-bio-Chemical Insight: Reviewing Interactions between Dietary Polyphenols and Gut Microbiota - Mahajan, Rishi; Attri, Sampan; Mehta, Vineet; Udayabanu, Malairaman; Goel, Gunjan (Mini Reviews in Medicinal Chemistry, 2018)
Objective: Polyphenols are widespread constituents of different food commodities. These are regarded as essential micronutrients because of their well-documented health benefits. These health benefits depend on the amount of polyphenols consumed and their bioavailability in the gut. The microbial transformation of polyphenols in gut is poorly characterized, where, these polyphenols may act as promoting factors for proliferation of beneficial gut inhabitants and inhibiting the pathogenic species. Conclusion: The aim of this review is to present a holistic view on occurrence of polyphenols, their health benefits and influence of dietary polyphenols on gut microbiota.
Keywords: biotransformation